Upgrading of anaerobic digestion of waste activated sludge by a hyper-thermophilic–mesophilic temperature-phased process with a recycle system. Issue 84 (16th September 2015) - Wu, L. J.; Qin, Y.; Hojo, T.; Li, Y. Y.
<x xml:space="preserve">Abstract</x> A hyper-thermophilic–mesophilic temperature-phased anaerobic digestion with a recycle system effectively upgraded the mesophilic digestion of waste activated sludge.